MANIPULASI CAHAYA UNTUK MENURUNKAN KELIMPAHAN NEMATODA PARASIT TUMBUHAN PADA Pembibitan KOPI - I Gede Swibawa, Dwisyah Putra, F.X. Susilo, Kurniatun Hairiah & Didik Suprayogo. (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2010)
Light manipulation to reduce the plant parasitic nematodes abundance on coffee nursery. Plant parasitic nematode problem on monoculture coffee can be caused not only by the suitable hosts but also by the environmental changes, such as soil water content and soil temperature. A semi-field experiment was conducted in Sumberjaya, West Lampung on May-September 2007 with the aim to study the effect of shading levels and fertilizer levels of coffee nursery on plant parasitic nematodes abundance. The results showed that the shading level treatment on coffee nursery significantly affected the abundance of plant parasitic nematodes but did not affect the free-living nematode abundance. The relationship between the plant parasitic nematode abundance with the shading level is polynomial with the highest nematode abundance (500 individual/300 ml of soil) was under 40% shading level. The increase in shading level indirectly affected the increase in plant parasitic nematode abundance through the increas in of soil water content. Inorganic N, P and K fertilizer at the recommended level for coffee nursery increased the abundance of plant parasitic nematodes from 216 to 282 individual/300 ml of soil. The interaction between the shading level and fertilizer did not significantly affect the plant parasitic nematode abundance.